2014
DOI: 10.1016/j.jnutbio.2013.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Liquid fructose down-regulates liver insulin receptor substrate 2 and gluconeogenic enzymes by modifying nutrient sensing factors in rats

Abstract: High consumption of fructose-sweetened beverages has been linked to a high prevalence of chronic metabolic diseases. We have previously shown that a short course of fructose supplementation as a liquid solution induces glucose intolerance in female rats. In the present work, we characterized the fructose-driven changes in the liver and the molecular pathways involved. To this end, female rats were supplemented or not with liquid fructose (10% w/v) for 7 or 14 days. Glucose and pyruvate tolerance tests were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Several studies indicate that exposure of liver cells to high glucose, fructose or sucrose content induce hepatic insulin resistance in rodent 99,100 which can be the consequence of decreased insulin receptor expression or increased phosphorylation of the insulin receptor substrate (IRS)1 therefore suppressing insulin receptor signaling 101,102 . The deleterious effects of chronic hyperglycemia on insulin sensitivity have been linked, among others, to oxidative stress, inflammation and ER stress 103 .…”
Section: ) Harmful Effects Of Hepatotoxic Carbohydratesmentioning
confidence: 99%
“…Several studies indicate that exposure of liver cells to high glucose, fructose or sucrose content induce hepatic insulin resistance in rodent 99,100 which can be the consequence of decreased insulin receptor expression or increased phosphorylation of the insulin receptor substrate (IRS)1 therefore suppressing insulin receptor signaling 101,102 . The deleterious effects of chronic hyperglycemia on insulin sensitivity have been linked, among others, to oxidative stress, inflammation and ER stress 103 .…”
Section: ) Harmful Effects Of Hepatotoxic Carbohydratesmentioning
confidence: 99%
“…Thus, although caution is needed when extending results of animal studies to humans, rats are useful models to understand the molecular mechanisms underlying the metabolic derangements caused by high-fructose diets. We have previously shown that the administration of a 10% w/v fructose solution to female rats caused hyperinsulinaemia, glucose intolerance, reduced insulin receptor substrate-2 (IRS-2) hepatic expression, and hepatic steatosis, which we attributed to the induction of carbohydrate response element binding protein (ChREBP) 10 11 . In these studies, fructose was administered for 14 days, which is a short treatment period given that fructose consumption patterns in humans extend over many years.…”
mentioning
confidence: 95%
“…Our research group has shown that liquid fructose supplementation in female rats fed a standard chow diet (two weeks to two months) induces glucose intolerance and IR [12,13,14,15]. However, unhealthy human dietary patterns frequently include not only excessive added sugars, but also excessive fat intake, particularly saturated fats [16].…”
Section: Introductionmentioning
confidence: 99%